2015
DOI: 10.1038/srep18211
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNP analysis explains coral diversity and recovery in the Ryukyu Archipelago

Abstract: Following a global coral bleaching event in 1998, Acropora corals surrounding most of Okinawa island (OI) were devastated, although they are now gradually recovering. In contrast, the Kerama Islands (KIs) only 30 km west of OI, have continuously hosted a great variety of healthy corals. Taking advantage of the decoded Acropora digitifera genome and using genome-wide SNP analyses, we clarified Acropora population structure in the southern Ryukyu Archipelago (sRA). Despite small genetic distances, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 49 publications
6
74
1
Order By: Relevance
“…Such disagreement between genetic connectivity and geographic distance in the A. digitifera populations were also reported in Nishikawa and Sakai () within the southern Nansei Archipelago. Shinzato et al () concluded from the decoded genome of A. digitifera that the population structure in the southern Nansei Archipelago is influenced by infrequent long‐distance dispersal over the SRA. They detected strong historical migration from the Yaeyama Islands (YIs) to Okinawa Island.…”
Section: Discussionmentioning
confidence: 99%
“…Such disagreement between genetic connectivity and geographic distance in the A. digitifera populations were also reported in Nishikawa and Sakai () within the southern Nansei Archipelago. Shinzato et al () concluded from the decoded genome of A. digitifera that the population structure in the southern Nansei Archipelago is influenced by infrequent long‐distance dispersal over the SRA. They detected strong historical migration from the Yaeyama Islands (YIs) to Okinawa Island.…”
Section: Discussionmentioning
confidence: 99%
“…Low quality bases (Phred quality score <30) were trimmed using SolexaQA (Cox et al, 2010) and high-quality sequences longer than 200 bp were retained for subsequent analyses. To identify Acropora species from eDNA, we used mtCR sequences based on the complete, assembled, mitochondrial genomes of corals used in this study (see above) and on A. digitifera sequencing data from five individuals previously collected at Kabira, Ishigaki, Japan (Shinzato et al, 2015). Although mtCR is highly variable within Acropora mitochondrial genomes ( Figure S2), percent identities of mtCR sequences between species are high (88.5-100%, Table S2).…”
Section: Pcr Amplicon Sequencing and Bioinformatics Analysismentioning
confidence: 99%
“…Due to the symbiont natural rates of increase, corals steadily release Symbiodinium cells into the surrounding environment (Yamashita et al, 2011), suggesting that close to reefs, seawater should contain detectable quantities of DNA from both corals and Symbiodinium. Recently, whole genome sequences of an Acropora coral (Shinzato et al, 2011) and Symbiodinium (Shoguchi et al, 2013;Lin et al, 2015;Aranda et al, 2016) have been published, and nextgeneration sequencing (NGS) technologies have been used to investigate coral reef biodiversity (Shinzato et al, 2014b(Shinzato et al, , 2015Combosch and Vollmer, 2015;Bongaerts et al, 2017). In the genus Symbiodinium, each clade contains multiple genetic types, and identification has been performed using ribosomal, mitochondrial, plastid, and nuclear DNA markers (Rowan and Powers, 1991;Wilcox, 1998;Lajeunesse, 2001;Santos et al, 2002;Takabayashi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…; Shinzato et al. ). Furthermore, while transplantation of coral fragments has been one of the most frequently recommended approaches to enhance coral abundance on degraded reefs (Omori and Fujiwara ; Rinkevich ; Young et al.…”
Section: Introductionmentioning
confidence: 96%